North Korea and the geopolitics of development - Gray, Kevin, 1973-; Lee, Jong-Woon (Cambridge ; New York, NY : Cambridge University Press, 2021)
Introduction: The development-geopolitics nexus in North Korea -- State building and late development in North Korea -- Post-war reconstruction and catch-up industrialisation -- Geopolitical contestation and the challenge to North Korean development -- Economic decline and the crisis of the 1990s -- Marketisation and the transformation of the North Korean state -- North Korean economic reform in the shadow of China -- Dependency in Chinese-North Korean relations? -- International sanctions and North Korean development.
Includes bibliographical references and index.
Buku bacaan asas fakulti.
Keywords: Economic development -- Korea (North).; Geopolitics -- Korea (North).; Geopolitics -- East Asia; Korea (North) -- Economic conditions; Korea (North) -- Politics and government; Korea (North) -- Foreign economic relations